Association between eating habits and low physical activity in adolescents - Đurđević Dragan; Nikolić Aleksandra; Mazić Sanja; Šipetić-Grujičić Sandra (Vojnosanitetski Pregled)
Background/Aim. Insufficient levels of physical activity and poor nutrition, have led to an increase in the number of obese adolescents and cardiometabolic problems. The aim of this study was to analyze the association between eating habits and low physical activity levels among adolescents. Methods. The cross-sectional study, conducted in May 2017, included a total of 389 participants, aged 15–19 years. The study instrument was a questionnaire regarding demographic characteristics, physical activity (International Physical Activity Questionnaire-Short Form), as well as eating habits. The data were analyzed using univariate and multivariate logistic regression analysis. Results. A total of 131 participants (33.7%) had a low level of physical activity, and 258 (66.3%) had a moderate/high level of physical activity. Adolescents with moderate/high physical activity were significantly more likely to be male and medical school students. Moreover, they had breakfast significantly more often, consumed fish more than twice a week or at least twice a week, ate fruit once a day or more, and generally ate healthy, compared to the high school students with low physical activity. Among the factors associated with low physical activity were the following: the female gender, eating breakfast never/sometimes, consuming fish less than twice a week, fruit less than once a day, maintaining a healthy diet, and adolescents aged 18–19 years. Conclusion. This study identified several statistically significant independent factors associated with low physical activity in adolescents. Based on the obtained results, it is necessary to undertake certain interventions, promote physical activity, correct eating habits, and the overall lifestyle, with a special emphasis on the female population and teenagers aged 18–19 years. The education of both adolescents and their parents is essential.